2022
DOI: 10.1007/s40692-022-00224-0
|View full text |Cite
|
Sign up to set email alerts
|

E-content development of English language courses during COVID-19: a comprehensive analysis of students’ satisfaction

Abstract: There was a sudden switch to online learning approaches because of the COVID-19 pandemic. Universities were under pressure to provide a variety of e-learning designs during a short time, impacting the quality of the learning. This study tended to evaluate the quality of e-content development related to English language courses by Shiraz University of Medical Sciences (SUMS) faculties. The survey was conducted on 610 undergraduate students of SUMS who had an English course in the first semester which was during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Jensen et al stated that only the use of face‐to‐face or electronic methods does not guarantee its effectiveness, but in fact, it was the amount of interaction between the teachers and the students that made a combined course effective (Jensen et al, 2015 ). In the research of Khojasteh et al ( 2023 ) the results showed that the most important determining factor was the effectiveness of interactions between teachers and students.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al stated that only the use of face‐to‐face or electronic methods does not guarantee its effectiveness, but in fact, it was the amount of interaction between the teachers and the students that made a combined course effective (Jensen et al, 2015 ). In the research of Khojasteh et al ( 2023 ) the results showed that the most important determining factor was the effectiveness of interactions between teachers and students.…”
Section: Discussionmentioning
confidence: 99%
“…This point was also mentioned in the qualitative comments of the participants in this study. In a similar vein, Khojaste et al (2022) reported that the level of students' access to electronic tools and devices affects their satisfaction with the quality of the course [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…E-content, the second element of virtual education preferences, accounts for 13% of the overall variance. The majority of research highlights the value of pre-prepared e-content, which is highly preferred due to its adaptability to time and place as well as the needs of students [ 44 , 45 ]. Another consideration is that multimedia e-content enhances learning by engaging different sensory channels [ 46 ], is better suited to students' learning preferences, and gives them a more enjoyable learning experience [ 47 ].…”
Section: Discussionmentioning
confidence: 99%